Analisa Penerapan Konsep Kaizen 5S Terhadap Efektivitas Kerja Menggunakan Uji Regresi Linier Berganda - Sugih Mulyana; Asep Erik Nugraha; Wahyudin Wahyudin (Program Studi Teknik Industri Universitas Setia Budi, 2023)
Standardization of 5S (Seiri, Seiton, Seiso, Seiketsu and Shitsuke) and waste elimination (Muda) are the 3 main pillars of gemba Kaizen in improvement with a common sense and low cost approach. Dirty and unkempt machines, dirty work environment are some of the problems faced by PT. XYZ. All of this causes a waste of both cost and time. Poor workplace management can also lead to waste. Discipline and morale of the workers are also one of the problems that exist in PT. XYZ. Lack of awareness and discipline of employees can be seen in the ongoing production activities. This study uses a case study method which is part of an interactive qualitative research method that applies the 5S concept in solving problems and uses a linear regression test which aims to determine the significant effect of the simultaneous and dominant 5S Kaizen concept on the work effectiveness of PT. XYZ. The results showed that the concept of Kaizen 5S simultaneously had a significant effect on work effectiveness. While the variables that have the most dominant influence on work effectiveness.